2007
DOI: 10.2174/157016107779317161
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1-Induced Signaling Pathways in Vascular Smooth Muscle Cells

Abstract: Endothelin-1 (ET-1), a vasoactive peptide, is believed to contribute to the pathogenesis of vascular abnormalities such as hypertension, atherosclerosis, hypertrophy and restenosis. ET-1 elicits its biological effects through the activation of two receptor subtypes, ET-A and ET-B that belong to a large family of transmembrane guanine nucleotide-binding protein-coupled receptors (GPCRs). ET-1 receptor activation results in the stimulation of several signaling pathways including mitogen-activated protein kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 89 publications
4
129
0
2
Order By: Relevance
“…ET-1 therefore contributes to the abnormal proliferation of PASMCs in PAH. When ET-1 binds its receptor, vasoconstriction and cell proliferation results in response to activation of phospholipase-C β and the second messengers diacylglycerol and Ins(1,4,5)P 3 by activating calcium channels (18). ET-1 binding also stimulates MAPK family signaling events by first activating the small guanosine triphosphates (GTPases) Ras and Raf, leading to phosphorylation of downstream MAP kinases followed by phosphorylation of extracellular signal-regulated kinase (ERK) 1/2 (see Figure 1).…”
Section: Et-1mentioning
confidence: 99%
See 1 more Smart Citation
“…ET-1 therefore contributes to the abnormal proliferation of PASMCs in PAH. When ET-1 binds its receptor, vasoconstriction and cell proliferation results in response to activation of phospholipase-C β and the second messengers diacylglycerol and Ins(1,4,5)P 3 by activating calcium channels (18). ET-1 binding also stimulates MAPK family signaling events by first activating the small guanosine triphosphates (GTPases) Ras and Raf, leading to phosphorylation of downstream MAP kinases followed by phosphorylation of extracellular signal-regulated kinase (ERK) 1/2 (see Figure 1).…”
Section: Et-1mentioning
confidence: 99%
“…ET-1 binding also stimulates MAPK family signaling events by first activating the small guanosine triphosphates (GTPases) Ras and Raf, leading to phosphorylation of downstream MAP kinases followed by phosphorylation of extracellular signal-regulated kinase (ERK) 1/2 (see Figure 1). Phosphorylation of ERK 1/2 results in p 38 MAPK and c-Jun terminal kinase activation that promotes growth signaling and controls cell survival and differentiation (18).…”
Section: Et-1mentioning
confidence: 99%
“…This results in the activation of signaling pathways that include, phospholipase A 2 , phospholipase C and further downstream protein kinase C, calmodulin, phosphatidylinositol 3-kinase and mitogenactivated protein kinases. [6][7][8][9] Receptors for ET-1 are expressed not only in smooth muscle cells but also in adipocytes and a number of other tissues. 6,10 It has recently been shown that ET-1 is released by human subcutaneous (s.c.) adipose tissue and that its secretion is elevated in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore investigated whether ET-1 is released by adipose tissue and may influence the antilipolytic effect of insulin in adipocytes from the visceral (omental [OM]) and subcutaneous (SC) regions. ET-1 binds to the Gq-protein coupled receptors endothelin receptor-A (ET A R) and -B (ET B R), which both mediate signaling pathways that include phospholipase C and, further downstream, protein kinase C or calmodulin (17)(18)(19). We also investigated which ETR and intracellular signaling pathways mediate the effect of ET-1 on insulin-induced antilipolysis.…”
mentioning
confidence: 99%